Association of some weather factors with fish assemblage in Asejire Lake, South-western Nigeria - Ipinmoroti, Mabel Omowumi; Iyiola, Adams Ovie; Akanmu, Olumuyiwa Ayodeji (Journal of Agriculture and Environmental Sciences, 2022)
With the increasing human population, it is important to investigate the condition of Asejire Lake for sustainability. To this end, the effects of some weather factors were investigated on the fish assemblage, so as to provide necessary information to complement the dearth of reports about weather factors on the Lake. The study area was partitioned into three stations (upper, middle and lower) with fortnight collection of water samples, fish sampling and weather parameters for a period of 12 months (November 2017 – October 2018). Water samples were measured in situ using appropriate kits for pH, ammonia, nitrite and nitrates, dissolved oxygen and water temperature. Monofilament gill nets (40 mm and 60 mm) were used for fish sampling and were sorted and identified using appropriate monographs. The mean values across the sampling stations for temperature, pH, dissolved oxygen, ammonia, nitrates and nitrites were 18.36 ± 0.41oC, 7.30 ± 0.06, 2.37 ± 0.10 mg/L, 1.25 ± 0.05 mg/L, 1.34 ± 0.33 mg/L and 0.31 ± 0.03 mg/L, respectively. Across the months, mean values were 17.94 ± 0.48 oC, 2.67 ± 0.21 mg/L, 7.22 ± 0.21, 0.23 ± 0.02 mg/L, 0.13 ± 0.02 mg/L and 3.03 ± 0.03 for temperature, DO, pH, ammonia, nitrite and nitrates, respectively, with significant values (P < 0.05) among some parameters. A total of 1443 individual fishes (720 in the dry and 723 in the wet season) belonging to 27 species were encountered. March had the highest overall relative abundance of fish (23.77%) with Chrysichthys nigrodigitatus being the most abundant species (39.32%). March (47.64%) and April (32.78%) recorded the highest fish abundance in the dry and wet seasons respectively. Rainfall (540 mm) and temperature (35.50 °C) were highest in the month of September. The trend of rainfall and temperature was observed to increase over the months with t-values of 1.77 and 1.64 respectively. A negative relationship was observed between fish abundance with temperature (b1= -1.08) and rainfall (b1 = -0.26). It was observed that temperature values increased and rainfall values varied. Therefore, activities must be geared towards environmental management and consciousness of aquatic resources because of sustainability.